Pre-Service Training of Elementary School Teachers for Organization of Inclusive Learning Environment - Sergiy Sydoriv (Vasyl Stefanyk Precarpathian National University, 2022)
The paper highlights the ongoing challenges and barriers of training teachers to implement inclusive education in various types of schools. The study has identified theoretical aspects and the importance of professional training of future elementary school teachers to organize an inclusive educational environment. It has produced an analysis of the international and national legislative and normative documents that regulate and support inclusion in educational institutions of Ukraine. The author has performed a substantial analysis of scholarly texts and publications on the researched topic and defined the present challenges in psychological and pedagogical theory in historical and pedagogical context. Considerable attention is paid to the study of research of Ukrainian scholars on organization of education activities and use of innovative pedagogical technologies in the context of including persons with special educational needs and disabilities (SEND). Various aspects of training pre-service teachers for effective implementation of inclusive education have been outlined: individualization of instructing in an inclusive classroom, use of information and communication technologies, application of art and music therapy tools for special needs services and speech therapy activities for development of language and speech skills in preschoolers and elementary school students, organizational and methodological foundations of special education and rehabilitation settings of universities, teacher training institutes and colleges. It has been proved that the prerequisite for effective socialization and inclusion of students with special educational needs and disabilities (SEND) is the development and sustainability of a proper nurturing inclusive environment, and hence the multidisciplinary psychological and pedagogical support for students with SEND is vital. The emphasis is placed on the use of effective innovation strategies and practices, the development of a coordinated program of pre-service and in-service teacher training, mutual interaction and cooperation (local and international) in an inclusive educational community. It has been found that the creation of an effective inclusive educational environment in modern elementary schools is determined by the level of professional capacity and motivation of teachers to implement relevant tasks in practice.